The effects of hybrid online planning and L2 proficiency on video-based speaking task performance. Issue 1 (13th November 2020) - Wang, Zhan; Skehan, Peter; Chen, Gaowei
Abstract : This study investigated L2 speaking performance under three different types of task-related time pressure, with a control (Control) group narrating a video at normal playing rate, an online planning (OP) group narrating the video at a slowed playing rate, and a hybrid online planning (HOP) group which combined online planning (a slowed playing rate) with content preparedness (through prewatching the video). The results show that the HOP group outperformed the Control group regarding speech accuracy and complexity, suggesting that this form of online planning, with content preparedness, helps improve speech accuracy and complexity. In addition, L2 proficiency significantly predicted speech accuracy, specifically, among all other performance measures. The implications of these findings for language teaching and learning are discussed, particularly their relevance for the way a Conceptualiser-Formulator balance is important, and for the way proficiency can best be mobilised within task performance.